2011
DOI: 10.4028/www.scientific.net/amm.146.12
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Whiskers Micro-Fibers Effect in the Mechanical Proprieties of PP and PLA Composites Fibers Obtained by Spinning Process

Abstract: In this study, we present the manufacturing process of two new composites materials in the form of long fibers of polylactic-acid (PLA) or polypropylene (PP), reinforced by cellulose whiskers micro-fibers loads. In order to evaluate the mechanical properties of these advanced materials, a several uniaxial tensile tests were carried out. The PP and the PLA have initially been spinning without the addition of cellulose whiskers micro-fibers. In order to study the effects of cellulose whiskers micro-fibers reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…This increment suggests that MCC contributes to the mass of the composite lament due to its inherent density and rigidity. This is also supported by previous ndings (González et al, 2023) (Korkmaz Memiş & Kaplan, 2021) (Gherissi et al, 2012). Furthermore, SMPU-MCC microcomposite laments with draw ratio of 3.2 exhibit the lowest linear density (170.2dtex at original shape and 168.6dtex at xed temporary shape), suggesting that higher draw ratios decrease mass per unit length of the laments.…”
Section: Physical and Mechanical Properties Of Filamentssupporting
confidence: 86%
“…This increment suggests that MCC contributes to the mass of the composite lament due to its inherent density and rigidity. This is also supported by previous ndings (González et al, 2023) (Korkmaz Memiş & Kaplan, 2021) (Gherissi et al, 2012). Furthermore, SMPU-MCC microcomposite laments with draw ratio of 3.2 exhibit the lowest linear density (170.2dtex at original shape and 168.6dtex at xed temporary shape), suggesting that higher draw ratios decrease mass per unit length of the laments.…”
Section: Physical and Mechanical Properties Of Filamentssupporting
confidence: 86%
“…The extraction of CMF from Alfa plant was carried out following a protocol that was described by Ben Brahim and Ben Cheikh [28] and Gherissi et al. [30].…”
Section: Methodsmentioning
confidence: 99%
“…All these methods lead to different types of CNF, depending on the cellulose raw materials, its pre-treatment, and on the disintegration process [27]. The use of Alfa fibres to produce nanocomposites using thermoplastic materials has been recently published [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its many advantages, still, PLA has several demerits, such as brittleness, poor toughness, poor impact strength, and poor gas and moisture barrier properties [17]. It is known that by the addition of a few percents of nano to micro-sized particles, the tensile strength of thermoplastic polymers can be considerably increased [18,19]. It was reported that the addition of cellulose nanocrystals to PLA increased its toughness and biodegradability [20].…”
Section: Introductionmentioning
confidence: 99%